Measurement of Bone Mineral Density in Children with Cerebral Palsy from an Ethical Issue to a Diagnostic Necessity - Nurković, Jasmin S. (Biomed Res Int, 2020)
INTRODUCTION: Due to concerns about cumulative radiation exposure in the pediatric population, it is not standard practice to perform dual-energy X-ray absorptiometry (DXA) analysis in the diagnostic process of musculoskeletal disorders, such as cerebral palsy (CP). This study aimed to evaluate the bone mineral density (BMD) in children with CP and the ethical justification of applying DXA analysis in these children. Material and Methods. In this monocentric retrospective analysis, data were collected from children and adolescents with CP who were treated for a primary illness for three years. A clinical examination, which included a DXA analysis, recommended by the multidisciplinary team, was performed. After applying inclusion and exclusion criteria, 60 scans remained for statistical analysis. BMD and Z-scores for the lumbar spine (LS), and hip right and left femoral neck (RFN and LFN, respectively), and total hip (TH) were recorded. RESULTS: The average age of children with CP when DXA analysis was first performed was about 7 years. The BMD (mean ± SD) at LS (LS-BMD) of all patients was 0.612 ± 0.12, at RFN 0.555 ± 0.11, at LFN 0.572 ± 0.1, and at TH (TH-BMD) 0.581 ± 0.13. The values of the Z-score (mean ± SD) at LS of all patients were −2.5 ± 0.22, at RFN −2.2 ± 0.21, at LFN -2.25 (SD = 0.2), and at TH -2.3 (SD = 0.23). There was no statistical significance between age and gender; however, BMI, walking ability, fracture history, and pattern of CP had a significant impact on BMD and Z-score values of these children. CONCLUSION: The results of our study clearly indicate that children with CP have a higher risk of low BMD, osteoporosis, and bone fractures, which makes it ethically justifiable to perform the DXA analysis in these children.